Direct visualization of atomically precise nitrogen-doped graphene nanoribbons - Zhang, Yi; Zhang, Yanfang; Li, Geng; Lu, Jianchen; Lin, Xiao; Du, Shixuan; Berger, Reinhard; Feng, Xinliang; Muellen, Klaus; Gao, Hong-Jun (Applied Physics Letters, 2014)
We have fabricated atomically precise nitrogen-doped chevron-type graphene nanoribbons by using the on-surface synthesis technique combined with the nitrogen substitution of the precursors. Scanning tunneling microscopy and spectroscopy indicate that the well-defined nanoribbons tend to align with the neighbors side-by-side with a band gap of 1.02 eV, which is in good agreement with the density functional theory calculation result. The influence of the high precursor coverage on the quality of the nanoribbons is also studied. We find that graphene nanoribbons with sufficient aspect ratios can only be fabricated at sub-monolayer precursor coverage. This work provides a way to construct atomically precise nitrogen-doped graphene nanoribbons. © 2014 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20